Impact of diabetes and hypertension on cardiovascular outcomes in patients with coronary artery disease receiving percutaneous coronary intervention. Issue 1 (December 2017) - Lin, Mao-Jen; Chen, Chun-Yu; Lin, Hau-De; Wu, Han-Ping
Abstract Background Percutaneous coronary intervention (PCI) is a necessary procedure commonly performed for patients with coronary artery disease (CAD). However, the impact of diabetes and hypertension on long-term outcomes of patients after receiving PCI has not yet been determined. Methods The data of 1234 patients who received PCI were collected prospectively, and patients were divided into four groups, including patients with and without DM and those with either DM or hypertension alone. Baseline characteristics, risk factors, medications and angiographic findings were compared and determinants of cardiovascular outcomes were analyzed in patients who received PCI. Results Patients with DM alone had the highest all-cause mortality (P  < 0.001), cardiovascular mortality and myocardial infarctions (MI) (bothP  < 0.01) compared to the other groups. However, no differences were found between groups in repeat PCI (P  = 0.32). Cox proportional hazard model revealed that age, chronic kidney disease (CKD), previous MI and stroke history were risk factors for all-cause mortality (OR: 1.05, 1.89, 2.87, and 4.12, respectively), and use of beta-blockers (BB) and statins reduced all-cause mortality (OR: 0.47 and 0.35, respectively). Previous MI and stroke history, P2Y12 inhibitor use, and syntax scores all predicted CV mortality (OR: 4.02, 1.89, 2.87, and 1.04, respectively). Use of angiotensin converting enzyme inhibitors (ACEI), beta-blockers (BB), and statins appeared to reduce risk of CV death (OR: 0.37, 0.33, and 0.32, respectively). Previous MI and syntax scores predicted MI (OR: 3.17 and 1.03, respectively), and statin use reduced risk of MI (OR: 0.43). Smoking and BB use were associated with repeat PCI (OR: 1.48 and 1.56, respectively). Conclusions After PCI, patients with DM alone have higher mortality compared to patients without DM and hypertension, with both DM and hypertension, and with hypertension alone. Comorbid hypertension does not appear to increase risk in DM patients, whereas comorbid DM appears to increase risk in hypertensive patients. Trial registration REC103-15 IRB ofTaichung Tzu-chi Hospital